Perancangan dan Implementasi Website Pariwisata di Desa Sembulang dengan Metode Extreme Programming - Dannis Wongso (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
Geographical information system or GIS is a geographic system that has been widely used, especially by tourists or tourists. In this study, GIS was used to map Sembulang village with the aim of reaching tourist attractions in Sembulang village to tourists, both from within the country and from abroad. It is hoped that with a geographic information system that can attract visitors to the tourist attractions of Sembulang village. This system is built using the programming language HTML, Javascript, and CSS and uses several assistance applications such as XAMPP and Sublime Text Editor.